Development of a 2-Stroke GDI Engine. (September 2017) - Savioli, Tommaso; Zardin, Barbara; Borghi, Massimo
Abstract: Nowadays, high-pressure gasoline direct injection (GDI) can be considered a standard technology, due to the wide application on 4-stroke turbocharged engines. This technology – in combination with other specific solutions - has been successfully applied to a 500 cc, 30 kW 2-stroke engine, initially developed as a range extender. The engine is valve-less and cam-less, being the scavenge and exhaust ports controlled by the piston. An electric supercharger delivers the required airflow rate, without need of a throttle valve; the lubrication is identical to a 4-stroke. The current study reviews the development process, assisted by CFD simulation, that has brought to the construction of a prototype, tested at the dynamometer bed of the University of Modena and Reggio Emilia (Engineering Department "Enzo Ferrari"). An experimentally calibrated CFD-1d model is applied to predict full load engine performance. The results show an excellent fuel efficiency and a very low level of thermal and mechanical stress despite the high power density.